2011
DOI: 10.1007/s00284-011-9945-x
|View full text |Cite
|
Sign up to set email alerts
|

Kanagawa-Negative, tdh- and trh-Positive Vibrio parahaemolyticus Isolated from Fresh Oysters Marketed in Fortaleza, Brazil

Abstract: Between October 2008 and June 2009, 15 samples of 10 live oysters each (Crassostrea rhizophorae) measuring 8.31-10.71 cm were purchased from a restaurant on the seashore of Fortaleza, Brazil. The Vibrio count ranged from 75 (estimated) to 43,500 CFU/g. Fourteen species were identified among the 56 isolated Vibrio strains, with V. parahaemolyticus as the most prevalent. Two of the 17 V. parahaemolyticus strains were urease-positive and tdh- and trh-positive on multiplex PCR, but neither produced β-hemolysis hal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 20 publications
0
13
0
2
Order By: Relevance
“…The variability in the incidence of different species of Vibrio may be related to the fact that this study was conducted in the warmer spring and summer seasons, whereas the other study covered all four seasons. Vieira et al 4 also observed a higher prevalence of V. parahaemolyticus (30.3% of those isolated) in the oyster samples.…”
Section: Seawater Parametersmentioning
confidence: 87%
See 2 more Smart Citations
“…The variability in the incidence of different species of Vibrio may be related to the fact that this study was conducted in the warmer spring and summer seasons, whereas the other study covered all four seasons. Vieira et al 4 also observed a higher prevalence of V. parahaemolyticus (30.3% of those isolated) in the oyster samples.…”
Section: Seawater Parametersmentioning
confidence: 87%
“…The only ureasepositive strain, which also contained the trh gene, has been previously described by other authors 4,34 . According to these studies, urease positivity is an indication of virulence.…”
Section: Seawater Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…parahaemolyticus is commonly found in commensal relationships with shellfish (13), free living in the water column (14), attached to surfaces (2,15), in sediments (14), and within infaunal burrows (16). Most "environmental" V. parahaemolyticus strains are considered to be nonpathogenic due to low detection frequencies of tdh and trh (1,17,18). This is illustrated by detection of the tdh and trh genes in only 4.3% and 0.3% (respectively) of environmental V. parahaemolyticus strains from highly populated areas of the South Carolina and Georgia coasts (19).…”
mentioning
confidence: 99%
“…The human pathogen Vibrio parahaemolyticus is commonly found associated with shellfish, particularly oysters (1,2). Depuration is a controlled process in which shellfish are placed into clean seawater to reduce the bacterial contaminants in their tissues.…”
mentioning
confidence: 99%